Sagot :
Answer:
=
−
±
2
−
4
√
2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b and c from the original equation and plug them into the quadratic formula.
1
5
2
−
7
−
2
=
0
15x^{2}-7x-2=0
15x2−7x−2=0
=
1
5
a={\color{#c92786}{15}}
a=15
=
−
7
b={\color{#e8710a}{-7}}
b=−7
=
−
2
c={\color{#129eaf}{-2}}
c=−2
=
−
(
−
7
)
±
(
−
7
)
2
−
4
⋅
1
5
(
−
2
)
√
2
⋅
1
5
Step-by-step explanation:Solution
=
2
3
=
−
1
5
Answer:
solving for
x
Step-by-step explanation:
x= -1 , 2
- -
5 3